Development of Mind Mapping Using Whimsical Application in Educational Digital Psychology Course - Ekaputra, Firdiawan; Dewi, Fitria; Afrida, Afrida (PT ARRUS Intelektual Indonesia, 2024)
The purpose of this research is to develop concept maps using whimsical applications in educational digital psychology courses. The method used in this research is the Research and Development method. The development model used in this research is the ADDIE model which consists of 5 stages including analysis, design, development, implementation, and evaluation. The subjects used in this study were one media expert, one material expert, and five students who had taken the educational digital psychology course to determine the quality of the media that had been developed. Based on the research that has been done, the development of mind mapping using whimsical applications in educational digital psychology courses is declared valid by media experts and material experts. The results of the media feasibility test in small groups obtained a result of 92.50 which means that it obtained very high criteria.